Eugenics, Race and Canada’s First-Wave Feminists: Dis/Abling the Debates - de la Cour, Lykke (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
Using government reports produced by one of Ontario’s pioneering women physicians and leading eugenic crusaders, Dr. Helen MacMurchy, this article interrogates the significance of disability as a central paradigm within first-wave feminism and its promotion of eugenic reforms. I examine how conceptualizations of race were reconstituted through the construct of disability to generate not only inter- but also intra-racial distinctions between differently classed white women. I argue that it was ultimately by leveraging a range of social categories —gender, class, race, and transgressive forms of sexuality—into a disabling paradigm that not only racialized women, but also poor white women were disempowered by eugenics.